Correction of near-surface methane concentrations using a CNN-RF hybrid model based on multi-scale feature extraction - Lu Fan; Yong Wan; Qian Xiao; Keyang Liu (Atmospheric Pollution Research, 2026)

Corrigendum to “Mechanisms of structural weakening and interfacial reconfiguration in the adsorption of methane from bituminous coal by anaerobic microorganisms in the presence of CO2” [Fuel 428 (2027) 140504] - Yundu Yang; Bingjun Liu; Junyu Wang; Sheng Xue; Chao Zhang; Yongqiang Yang; Keyang Cheng; Fengrong Wu; Wenshuai Ma (Fuel, 2026)

Associations between domestic water hardness and incident type 2 diabetes and the mediating role of metabolomics - Hanwen Zhou; Sicheng Li; Keyang Li; Wenlong Li; Yingcheng Liu; Rui Yu; Xufeng Xian; Wei Zheng; Xiaoni Zhong; Biao xie (Environmental Pollution, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

Corrigendum to “Amphiphilic colloidal particles/Ca2+ reinforced edible agar nanocomposite film by multiple cross-linking/microphase separation strategies” [Food Hydrocolloids, (159), February 2025, 110602] - Qingmei Zhu; Xiaona Su; Keyang Mai; Riting Huang; Shujuan Yang; Haifang Liu; Furui He; Yu Bao; Gaobo Yu; Yuhong Feng; Jiacheng Li (Food Hydrocolloids, 2026)

A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Toxicity multidimensional heterogeneity in antibiotic degradation: development and application of entropy-weighted evaluation strategy for advanced oxidation processes - Yufan Chen; Keyang Liu; Haijiao Xie (Water Research, 2026)

Insights into the effects of different nitrogen sources on microbial metabolic function and biodegradation of bituminous coal - Yundu Yang; Bingjun Liu; Sheng Xue; Junyu Wang; Xiangqing Jiang; Ruifeng Chen; Rui Sun; Keyang Cheng (Fuel, 2026)

A calculation method for the digital twin of aging jacket platforms within the digital healthcare engineering framework - Keyang Liu; Yuanchang Liu; Baoping Cai; Jeom Kee Paik (Ocean Engineering, 2026)

A risk-based early warning method for offshore platform equipment based on multi-source data fusion - Keyang Liu; Baoping Cai; Jeom Kee Paik (Ocean Engineering, 2025)

Biomass aerogel doped with FeS₂/MoS₂-modified anode for enhanced bioelectricity generation in microbial fuel cell and efficient treatment of high-concentration wastewater - Wenxia Zhai; Qian Gao; Ling Liu; Keyang Jiang; Sijia Zhu; Junxia Ni; Kaize Zhao; Wei Zhang; Zhaodong Qiu; Xi Liu; Zhiwei Wang (Journal of Environmental Chemical Engineering, 2025)

Cadmium exposure and health outcomes:An umbrella review of meta-analyses - Wenzhuo Xu; Sainan Wang; Wenhua Ruan; Mingyue Hao; Kele Jiang; Hao Guo; Anyi Geng; Mengting Man; Zheng Hu; Yun Liu; Guifang Jin; Haiyan Shi; et al. (Environmental Research, 2025)

Nacre-inspired gradient design and multifunctional wood-based composites using recycled GFRP from decommissioned wind turbine blades - Hualei Zhang; Yao Du; Dan Lu; Keyang Liu; Tiantian Zhang; Xiaohai Chen; Hongguang Liu; Li Li; Bin Luo (Chemical Engineering Journal, 2025)

Where the hope grows: strategies to fight cancer in China - Keyang Qian; Yujie Liu; Qiang Liu (Science China Life Sciences, 2025)

Mitigating nitrobenzene toxicity in anaerobic digestion using hollow carbon spheres: Enhanced methane production via direct interspecies electron transfer - Shunan Zhao; Keyang Li; Shaoqing Zhu; Qianli Guo; Ge Song; Kai Zhao; Qianming Gong; Ruiping Liu (Journal of Water Process Engineering, 2025)

Amphiphilic colloidal particles/Ca2+ reinforced edible agar nanocomposite film by multiple cross-linking/microphase separation strategies - Qingmei Zhu; Xiaona Su; Keyang Mai; Riting Huang; Shujuan Yang; Haifang Liu; Furui He; Yu Bao; Gaobo Yu; Yuhong Feng; Jiacheng Li (Food Hydrocolloids, 2025)

Dynamic host–guest/π–π multiple bonds of alginate-based super-amphiphiles reinforced the mechanical stability and foliar deposition of jammed emulsion droplet - Shujuan Yang; Furui He; Keyang Mai; Yan Zhou; Chaonan Shang; Haifang Liu; Yuhong Feng; Gaobo Yu; Jiacheng Li (Chemical Engineering Journal, 2025)

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

Urea-hydrolyzing Bacillus pasteurii microbially induced calcite precipitation for Ca2+ removal and enhanced anaerobic granular sludge activity in high-calcium wastewater - Jinhu Feng; Wenhao Dang; Qian Gao; Keyang Jiang; Sijia Zhu; Junxia Ni; Jian Zhang; Peng Lu; Weiqi Wei; Hainong Song; Xi Liu; Zhiwei Wang (Journal of Water Process Engineering, 2024)

Impact of phenolic-formaldehyde resin microplastics on anaerobic granular sludge: EPS interaction mechanisms and impacts on reactor performance - Keyang Jiang; Qian Gao; Jinhu Feng; Sijia Zhu; Wenxia Zhai; Di Wu; Huiya Zhang; Wei Zhang; Xi Liu; Jian Zhang; Shuangfei Wang; Zhiwei Wang (Journal of Hazardous Materials, 2024)

Exogenous signaling molecules N-acyl-homoserine lactones promotes the reconstruction of sludge particles after impact with highly concentrated urea-formaldehyde resin microplastics - Keyang Jiang; Xiao Yang; Qian Gao; Junxia Ni; Jinhu Feng; Di Wu; Xuelian Zou; Li Hu; Xi Liu; Zhaoping Song; Zhiwei Wang (Journal of Environmental Management, 2024)

Numerical investigation of thermodynamic effect on cavitation performance and cavitation-vortex interaction in an inducer - Bin Xu; Xingyu Liu; Keyang Liu; Weibin Zhang; Yilin Deng; Xi Shen; Desheng Zhang; B.P.M (Bart) van Esch (Ocean Engineering, 2024)

Effects of microencapsulated phase change materials on the thermal performance of gypsum board - Yan He; Keyang Liu; Mingjing Jiang; R.D. Hooton (Energy and Buildings, 2024)

Synergetic effect of biochar and intermittent electricity stimulation on mitigating the adverse effects of tannic acid on anaerobic granular sludge in wastewater - Junxia Ni; Yihu Xu; Keyang Jiang; Ling Liu; Yunpeng Zhu; Xuelian Zou; Qian Gao; Jinhu Feng; Di Wu; Xiaopeng Yue; Wei Zhang; Shuangfei Wang; et al. (Journal of Water Process Engineering, 2024)

Transitional bimetallic heterostructure catalyst modified anode for microbial fuel cell treatment of high-intensity wastewater - Ling Liu; Keyang Jiang; Yunpeng Zhu; Kaili Zhu; Xuelian Zou; Qian Gao; Junxia Ni; Jinhu Feng; Di Wu; Zhiwei Wang; Cuiping Mao (Journal of Environmental Chemical Engineering, 2024)

B ← N coordination bond reinforced dynamic fluorescence of pH-responsive amphiphile alginate aggregates for anti-counterfeiting - Riting Huang; Furui He; Shujuan Yang; Keyang Mai; Shuntian Huang; Haifang Liu; Yuhong Feng; Gaobo Yu; Jiacheng Li (Carbohydrate Polymers, 2024)

Ros-responsive dextran-phenylboronic acid-silibinin nanoparticles for targeting delivery of BAPTA-AM to effectively eliminate calcium overload-mediated inflammatory cascades and mitochondrial apoptosis: Alleviating acute liver injury - Yanan Wang; Huichao Wei; Keyang Li; Liru Liu; Yingfei Zhu; Xinyuan Wang; Jiahui Yan; Liangmin Yu; Xuefeng Yan; Zhiyu He (Chemical Engineering Journal, 2024)

Risk identification and assessment methods of offshore platform equipment and operations - Keyang Liu; Baoping Cai; Qibing Wu; Mingxin Chen; Chao Yang; Javed Akbar Khan; Chenyushu Wang; Hasini Vidumini Weerawarna Pattiyakumbura; Weifeng Ge; Yonghong Liu (Process Safety and Environmental Protection, 2023)

Physical properties of natural deep eutectic solvent and its application in remediation of heavy metal lead in soil - Kaiming Kang; Xiaoqiao Jia; Keyang Zheng; Xinyu Wang; Baoyou Liu; Yongjiang Hou (Journal of Contaminant Hydrology, 2023)

Thermodynamic effect on attached cavitation and cavitation-turbulence interaction around a hydrofoil - Bin Xu; Keyang Liu; Jiali Deng; Xingyu Liu; Xi Shen; Desheng Zhang; Ailian Chang; Jiuyu Chen; Sijiang Chang (Ocean Engineering, 2023)

Review of the mechanism and control methods of anaerobic granular sludge calcification - Zhiwei Wang; Keyang Jiang; Yunpeng Zhu; Ling Liu; Xuelian Zou; Xiao Yang; Yihu Xu; Jian Zhang; Yubao Chen; Wenhua Gao; Shuangfei Wang (Journal of Water Process Engineering, 2023)

Ambient PM2.5, ozone and mortality in Chinese older adults: A nationwide cohort analysis (2005–2018) - Yunquan Zhang; Zhouxin Yin; Shaojie Li; Junfeng (Jim) Zhang; Haitong Zhe Sun; Keyang Liu; Kokoro Shirai; Kejia Hu; Chengxuan Qiu; Xiaoyun Liu; Yachen Li; Yi Zeng; et al. (Journal of Hazardous Materials, 2023)

Nicosulfuron on the Atrazine-degrading Arthrobacter sp. DNS10 by assays of intracellular accumulation of substrates, Zeta potential, EPS, and stress responses - Shijie Deng; Qihang Zhou; Yuying Wang; Yuxin Liu; Keyang Xia; Bo Cao; Zhao Jiang; Ying Zhang (International Biodeterioration & Biodegradation, 2023)

A time series model adapted to multiple environments for recirculating aquaculture systems - Gedi Liu; Yifeng Jiang; Keyang Zhong; Yan Yang; Yang Wang (Aquaculture, 2023)

In vitro simulated digestion of and microbial characteristics in colonic fermentation of polysaccharides from four varieties of Tibetan tea - Yaowen Tan; Meiwen Li; Keyang Kong; Yushan Xie; Zhen Zeng; Zhengfeng Fang; Cheng Li; Bin Hu; Xinjie Hu; Caixia Wang; Saiyan Chen; Wenjuan Wu; et al. (Food Research International, 2023)

Light-dimerization telechelic alginate-based amphiphiles reinforced Pickering emulsion for 3D printing - Xinyu Zhao; Shujuan Yang; Furui He; Haifang Liu; Keyang Mai; Junhao Huang; Gaobo Yu; Yuhong Feng; Jiacheng Li (Carbohydrate Polymers, 2023)

Experimental Study on Unsteady Cavitating Flow and Its Instability in Liquid Rocket Engine Inducer - Hao Wang; Jian Feng; Keyang Liu; Xi Shen; Bin Xu; Desheng Zhang; Weibin Zhang (Journal of Marine Science and Engineering, 2022)
To study instability in the unsteady cavitating flow in a liquid rocket engine inducer, visualization experiments of non-cavitating and cavitating flows inside a model inducer were carried out at different flow conditions. Visual experiments were carried out to capture the evolution of non-cavitating and cavitating flows in a three-bladed inducer by using a high-speed camera. The external characteristic performance, cavitation performance, and pressure pulsation were analyzed based on the observation of non-cavitation and cavitation development and their instabilities. Under non-cavitation conditions, the change of flow rate has a significant impact on the pressure pulsation characteristics in the inducer. The occurrence of cavitation aggravated the instability of the flow and caused the intensity of pressure pulsation at each measuring point to increase. This cavitation structure has strong instability, and the tail region is often accompanied by shedding cavitation clouds perpendicular to the blade surface.

Improving the resolution of seismic data based on S-transform and modified variational mode decomposition, an application to Songliao Basin, Northeast China - Siqin Liu; Zhusheng Zhou; Sanxi Peng; Yang Yang; Weizu Zeng; Keyang Chen (Acta Geophysica, 2022)

Response to Antibiotic exposure and risk of type 2 diabetes mellitus: a systematic review and meta-analysis by Maryam et al. (2021) by J Zhou and K Chen (2021) - Jielin Zhou; Yan Lin; Yong Liu; Keyang Chen (Environmental Science and Pollution Research, 2022)

Antibiotic exposure and risk of type 2 diabetes mellitus: a systematic review and meta-analysis - Jielin Zhou; Yan Lin; Yong Liu; Keyang Chen (Environmental Science and Pollution Research, 2021)

Multi-proxy evidence of environmental change related to collapse of the Liangzhu Culture in the Yangtze Delta, China - Keyang He; Houyuan Lu; Guoping Sun; Xiang Ji; Yonglei Wang; Kaikai Yan; Xinxin Zuo; Jiangping Zhang; Bin Liu; Ningyuan Wang (Science China Earth Sciences, 2021)

Spatial distribution of atmospheric bioaerosols in Beijing, Hangzhou and Wuhan, China - Xuezheng Ma; Qi Zhang; Keyang Liu; Liping Zhang; Manman Zhang; Xin Zhao; Chunya Zhou; Jinke Li; Ming Cheng; Lili Li; Kongxin Hu; Jinsong Li; et al. (Aerobiologia, 2021)

Design and one-pot synthesis of 2-thiazolylhydrazone derivatives as influenza neuraminidase inhibitors - Keyang Yuan; Mengwu Xiao; Ying Tan; Jiao Ye; Yongle Xie; Xiaoxiao Sun; Aixi Hu; Wenwen Lian; Ailin Liu (Molecular Diversity, 2017)

Mechanism-Based Pharmacokinetic/Pharmacodynamic Model for THIOMAB™ Drug Conjugates - Siddharth Sukumaran; Kapil Gadkar; Crystal Zhang; Sunil Bhakta; Luna Liu; Keyang Xu; Helga Raab; Shang-Fan Yu; Elaine Mai; Aimee Fourie-O’Donohue; Katherine R. Kozak; Saroja Ramanujan; et al. (Pharmaceutical Research, 2015)